Asymptomatic Meibomian Gland Dysfunction and Cardiovascular Disease Risk Factors in a Middle-Aged Population in Taiwan - A Cross-sectional Analysis - Alexander Chen (Nature Portfolio, 2017)
Abstract Managing cardiovascular disease (CVD) risk factors is the key to prevent CVD. This study aimed to prevent CVD by introducing asymptomatic meibomian gland dysfunction (MGD), a condition associated with various CVD risk factors, as an early indicator for CVD in middle-aged population. Participants with and without asymptomatic MGD underwent standardized questionnaires, physical examinations, and laboratory investigations. One ophthalmologist completed the identification and grading of MGD by using slit-lamp biomicroscopy examination on the eyelid margins, meibomian gland orifices, and meibomian gland secretions. Standardized techniques were used to measure the CVD risk factor parameters. After adjusted for age and gender, CVD risk factors including elevated uric acid (P = 0.01), total cholesterol (Total-C, P < 0.001), low-density lipoprotein cholesterol (LDL-C, P < 0.001), fasting triglyceride (Fasting TG, P < 0.001), decreased high-density lipoprotein cholesterol (HDL-C, P = 0.04), and presence of hepatic steatosis (P = 0.008) were significantly associated with asymptomatic MGD. Stepwise logistic regression analysis revealed that LDL-C (OR: 1.03, 95% CI: 1.02–1.04) and Fasting TG (OR: 1.01; 95% CI: 1.00–1.01) levels were risk factors for having asymptomatic MGD (P < 0.001). Together, the results suggest that asymptomatic MGD may serve as an indicator for CVD.